Protocol for Language Arts Teaching Observation (PLATO) as a lens for assessing teaching quality - Klette, Kirsti; Luoto, Jennifer M.; Magnusson, Camilla G.; White, Mark C. (School effectiveness and school improvement, 2025)
In this study, we used the Protocol for Language Arts Teaching Observation (PLATO) tool to examine teaching quality in two consecutive Norwegian language arts lessons and two consecutive mathematics lessons to identify key patterns of teaching quality and how aspects of PLATO shaped findings. Our analyses reveal that the mathematics lessons receive consistently high scores on most PLATO elements while the patterns in the language arts lessons are more mixed of high and low scores fluctuating across different parts of the lessons. On the basis of this analysis, we discuss benefits and challenges with PLATO. A major strength of PLATO is the way aspects of teaching quality are conceptualized and defined at the level of elements, supported by precise and detailed rubrics, while challenges include the way PLATO privileges some instructional formats above others and how sequencing of the lessons into 15-min segments impacts findings and patterns identified.